Impact of workplace discrimination and harassment among National Health Service staff working in London trusts: results from the TIDES study. Issue 1 (16th December 2020) - Rhead, Rebecca D.; Chui, Zoe; Bakolis, Ioannis; Gazard, Billy; Harwood, Hannah; MacCrimmon, Shirlee; Woodhead, Charlotte; Hatch, Stephani L.
Abstract : Background: Harassment and discrimination in the National Health Service (NHS) has steadily increased over the past 5 years with London being the worst performing region. There is a lack of data and research on the impact this is having on staff health and job satisfaction. Such data are necessary to inform the development of effective workplace interventions to mitigate the effects these experiences have on staff. Aims: Examine the impact of harassment and discrimination on NHS staff working in London trusts, utilising data from the 2019 TIDES cross-sectional survey. Method: In total, 931 London-based healthcare practitioners participated in the TIDES survey. Regression analysis was used to examine associations between the sociodemographic characteristics of participants, exposure to discrimination and harassment, and how such exposures are associated with physical and mental health, job satisfaction and sickness absence. Results: Women, Black ethnic minority staff, migrants, nurses and healthcare assistants were most at risk of discrimination and/or harassment. Experiencing either of the main exposures was associated with probable anxiety or depression. Experiencing harassment was also associated with moderate-to-severe somatic symptoms. Finally, both witnessing and experiencing the main exposures were associated with low job satisfaction and long periods of sickness absence. Conclusions: NHS staff, particularly those working in London trusts, are exposed to unprecedented levels of discrimination and harassment from their colleagues. Within the context of an already stretched and under-resourced NHS, in order to combat poor job satisfaction and high turnover rates, the value of all healthcare practitioners must be visibly and continuously reinforced by all management and senior leaders.